Research progress of quercetin on anti-anxiety and anti-depression - Teng, Teng; Song, Chunhong (Frontiers in Pharmacology, 2025)
Anxiety and depression represent two of the most prevalent mental disorders worldwide, with current pharmacotherapies often limited by adverse effects and treatment resistance. Consequently, research into natural products for mental health interventions has attracted growing scientific interest. Quercetin, a bioactive flavonoid ubiquitously present in plant-derived flowers, fruits, and dietary sources, exhibits diverse pharmacological properties, including antioxidant, anxiolytic, and antidepressant activities. This review systematically summarizes the fundamental characteristics of quercetin, focusing on its core molecular mechanisms in alleviating anxiety- and depression-like behaviors, preclinical evidence from experimental models, and the current landscape of clinical investigations. By critically analyzing its therapeutic advantages, translational challenges, and emerging research priorities, this synthesis aims to offer a theoretical foundation for the development of quercetin-based formulations and their clinical implementation in mood disorder management.